The Social and Emotional Impact of Involving Individuals With Mental Illness in the Research Process. (September 2019) - Werner-Seidler, Aliza; Shaw, Frances
There is a need to involve individuals with a lived experience in health and medical research. Some organizations have developed mechanisms to seek the input of people with a lived experience. However, there are few examples of qualitative research into the impacts of participation. In this study, we investigate the social and emotional impact of participation on individuals, as well as the perceived impact on the organization, in an advisory panel at an Australian mental health research institute. In-depth qualitative interviews were conducted with 50% of the participants on the panel to understand how they conceptualized their involvement. Participants became invested in the organization and their role within it, and found it personally valuable to access diverse perspectives and discuss mental health outside a treatment context. These findings suggest that participating in the research process is beneficial to individuals with a lived experience of mental illness.